EFFICACY OF IMMUNOASSAY CHROMATOGRAPHY TEST FOR HEPATITIS-C ANTIBODIES DETECTION - Batool, Asia; Khan, Misbahul Islam; Bano, Khatoon Akhtar (Journal of Ayub Medical College Abbottabad, 2009)
Objective: To asses the efficacy of commercially available tests device method for anti HCV detection. Methods: Total 2000 blood samples for detection of anti HCV were screened initially by immunochromatographic method. Those found positive on initial screening were re-tested by ELISA method at the Biochemistry Laboratory of the Pakistan Medical Research Council, Fatima Jinnah Medical College, Lahore. Results: Out of a total of 2,000 blood samples, 177 were found to be initially reactive/positive for anti-HCV with immunochromatographic method. When these reactive/positive samples were retested for confirmation with ELISA, 47 blood samples were found to have tested falsely positive for anti-HCV. Overall 2.35% of blood samples were found to be tested false positive for anti-HCV by immunochromatographic device method. Conclusions: Immunochromatographic device method test is rapid and simple, which can be used in setting with limited facility when rapid testing is required. However it should not be used as sole criteria for diagnosis but should serve the purpose of initial screening only. Further research is required to establish the reliability of such devices for their specificity and sensitivity. Keywords: Immunochromatographic device test, Elisa testing method, anti-HCV, false positive